L-ASPARAGINASE INDUCED HYPOFIBRINOGENEMIA: A CASE REPORT - O, Balaji; Amita d; P, Navin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Anticancer therapy is always known to cause various side effects. L-asparaginase used in the treatment of adult T-cell lymphoblastic leukemia is a novel class of drug, an enzyme produced from plants as well as microorganisms except human. It is known to cause various adverse reactions including life-threatening neurological complications and thrombotic disorders. Hence, we report a case of hypofibrinogenemia associated with L-asparaginase in a patient treated for T-cell adult lymphoblastic leukemia. Â